Numerical and experimental study of natural convection heat transfer from a discrete heater array in an inclined/rotating liquid filled enclosure - Zhang, Xiaofen (2008)
The dissertation presents a three-dimensional computational model and experimental study of natural convection heat transfer from a 3X3 array of discrete heat sources, flush-mounted on one vertical wall of a rectangular cavity filled with liquid. The main thrust of dissertation focuses first on a stationary vertical enclosure, followed by inclinations and rotations covering conduction, natural convection and mixed convection regimes. The laminar model employs a semi-implicit finite volume formulation on a non-uniform staggered grid with a power law scheme. Scale analyses are performed to reveal useful information regarding the model behaviour, the physics of a transport process and the assessment of model parameters and heat transfer regimes. The model is verified successfully against experimental data obtained in the present work and those from literature.